2019
DOI: 10.1038/s41419-019-1504-6
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 promotes autophagy and glutaminolysis via stabilizing glutaminase

Abstract: Bcl-2 associated athanogene 3 (BAG3) is an important molecule that maintains oncogenic features of cancer cells via diverse mechanisms. One of the important functions assigned to BAG3 is implicated in selective macroautophagy/autophagy, which attracts much attention recently. However, the mechanism underlying regulation of autophagy by BAG3 has not been well defined. Here, we describe that BAG3 enhances autophagy via promotion of glutamine consumption and glutaminolysis. Glutaminolysis initiates with deaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Glutamine can be converted via GLS to glutamate, which can subsequently be converted to αketoglutarate to fuel the TCA cycle. Succinylation of GLS suppresses its K48-linked ubiquitination and degradation, stabilizing GLS and promoting glutaminolysis in cancer cells [295]. Study also found the function of supranutritional dose of selenite in suppressing tumor progression by promoting APC/C-CDH1 mediated GLS1 ubiquitination and degradation [296].…”
Section: Ubiquitination and Amino Acid Metabolismmentioning
confidence: 76%
“…Glutamine can be converted via GLS to glutamate, which can subsequently be converted to αketoglutarate to fuel the TCA cycle. Succinylation of GLS suppresses its K48-linked ubiquitination and degradation, stabilizing GLS and promoting glutaminolysis in cancer cells [295]. Study also found the function of supranutritional dose of selenite in suppressing tumor progression by promoting APC/C-CDH1 mediated GLS1 ubiquitination and degradation [296].…”
Section: Ubiquitination and Amino Acid Metabolismmentioning
confidence: 76%
“…Given their complimentary roles in autophagy (i.e., BAG3) and proteasomal degradation (i.e., BAG1), we next determined whether a downregulation in BAG3 was associated with a compensatory upregulation of BAG1 51 , 52 . In primary neurons expressing either Tat or Nef, no significant variation in BAG1 protein was observed, either by immunoblot or fluorescent microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we observed significant changes in the expression of Bcl-2 associated athanogene (Bag) proteins, which increase client release from Hsp70 by accelerating nucleotide exchange at the ATP site of this folding chaperone, in both naïve (ON) and influenza challenged (OF) aged cells. Here, we observed a striking difference in the expression pattern of Bag3 (Fig 10A, lower panel, black arrow), which is involved in regulating autophagy pathways (14,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77),…”
Section: Folding Components Differentially Regulated By Aging and Infmentioning
confidence: 93%